Caracterização da primeira microcina e de outras bacteriocinas sintetizadas por Shigella sonnei - Jaqueline Silvana Moreira (2014)
Shigella is the etiologic agent of shigellosis a severe type of inflammatory diarrhea. The disease is prevalent mainly among children aged up to five years that live in underdeveloped countries as a result from poor hygiene and sanitation. Bacteriocins are antibacterial proteinaceous substances synthesized by a wide range of bacteria including Shigella. A Shigella sonnei isolate (SS9) obtained from fecal specimen of a child with acute diarrhea previously tested for bacteriocin expression was selected for this study. Proteic intracellular fractions precipitated at 30 % (C-30) and 75 % (C-75) of ammonium sulfate were obtained. C-75 was submitted to sequential steps of chromatography that resulted in one purified fraction and some partially purified fractions. The molecular mass of the active fraction as determined by mass spectrometry was 7.2 kDa. The partial amino acid sequence of the substance was analyzed by using BLAST and BACTIBASE databases. The results showed that it corresponds to a new bacteriocin. The antagonistic substance corresponds to a microcin a class of bacteriocins not described for Shigella yet. SS9 expressed antagonistic activity mainly against taxonomically related strains. SDS-PAGE and in situ antagonistic activity test demonstrated that SS9 is able to synthesize more than one antagonistic substance. The evaluation of CIM and CBM as well as of the mode of action of the antagonistic substance(s) showed that SS9 exhibited bactericidal activity. Taken together our data suggest the expression of more than one colicin and microcin. It is reasonable to hypothesize that this ability may contribute to the virulence of S. sonnei helping in the competition against other enteropathogens or members of the intestinal microbiota.